¿Qué sabemos sobre las turberas peruanas? - López Gonzales, Mariela (2020)
Proyecto Mainstreaming Wetlands into the Climate Agenda: A multi-level approach (SWAMP-II). Subproyecto A Global Comparative Study for achieving effective, efficient and equitable REDD+ results.